2022
DOI: 10.1155/2022/3398732
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Pramipexole Combined with Nerve Growth Factor on Cognitive Impairment and Urinary AD7c-NTP Expression in Patients with Parkinson’s Disease

Abstract: Objective. To explore the effects of pramipexole combined with nerve growth factor (NGF) on cognitive impairment and urinary Alzheimer-associated neural thread protein (AD7c-NTP) expression in patients with Parkinson’s disease (PD). Methods. Fifty patients with PD treated in our hospital from February 2020 to April 2021 were enrolled. The patients were arbitrarily assigned into control group and study group. The former was treated with pramipexole, and the latter was treated with pramipexole combined with NGF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…miR-124 can protect dopaminergic neurons, and miR-137 can target dopamine receptors, and play an important role in the process of dopaminergic neuron proliferation and decline [14] . After the combined application of Madopar and Pramipexole, the miR-124 level and miR-137 in Parkinson's patients were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…miR-124 can protect dopaminergic neurons, and miR-137 can target dopamine receptors, and play an important role in the process of dopaminergic neuron proliferation and decline [14] . After the combined application of Madopar and Pramipexole, the miR-124 level and miR-137 in Parkinson's patients were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%